1975
DOI: 10.1111/1523-1747.ep12598018
|View full text |Cite
|
Sign up to set email alerts
|

Aspects Of Epidermal Ultrastructure

Abstract: Some problems posed by primarily ultrastructural studies of the epidermis are highlighted and discussed, and on the whole it is concluded that purely morphologic observations are unlikely further to elucidate such questions as the nature and function of keratohyalin, or the dynamic aspects of the general keratinization process. The contribution of freeze-fracture studies to the understanding of the functional morphology of the epidermis is assessed, with particular reference to specialized contacts, and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 58 publications
0
17
0
2
Order By: Relevance
“…More recent studies have concluded, however, that the most striking difference between desmosomes in the basal, spinous, and granular layers of epithelia is quantitative rather than qualitative: in the basal layer, desmosomes are fewer than in the more superficial strata (22)(23)(24)(25)(26)(27)(28)(29)(30). In fact, desmosome morphology appears to become markedly altered only as granular cells change into keratinized squame cells (29).…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies have concluded, however, that the most striking difference between desmosomes in the basal, spinous, and granular layers of epithelia is quantitative rather than qualitative: in the basal layer, desmosomes are fewer than in the more superficial strata (22)(23)(24)(25)(26)(27)(28)(29)(30). In fact, desmosome morphology appears to become markedly altered only as granular cells change into keratinized squame cells (29).…”
Section: Methodsmentioning
confidence: 99%
“…The lipid organization showing the lipid sheets was first observed under electron microscope [45,46,47], and later the regular stack of lamellar sheets was characterized [48,49]. Further understanding of the lipid organization of SC lipid lamellae was made possible by small- and wide-angle X-ray diffraction studies revealing the presence of a 13-nm lamellar phase and a long periodicity phase unique to the SC, and a 6-nm lamellar phase and a short periodicity phase in the SC lipid matrix.…”
Section: Lipid Organization In the Sc Lipid Lamellaementioning
confidence: 99%
“…The molecular arrangement of the stratum corneum lipids is also highly specialized: the skin barrier lipids do not form conventional bilayers but multilamellar membranes with the first lipid layer covalently anchored to the corneocyte surface (Breathnach, 1975;Grayson and Elias, 1982). In contrast to phospholipids, the stratum corneum ceramides have a small polar head and very long, saturated chains with prevailing alltrans conformation.…”
Section: Molecular Arrangement Of the Skin Lipid Barriermentioning
confidence: 99%